Transnational Japan in the Global Environmental Movement - Avenell, Simon (Book collections on Project MUSE., 2017)
What motivates people to become involved in issues and struggles beyond their own borders? How are activists changed and movements transformed when they reach out to others a world away? This adept study addresses these questions by tying together local, national, regional, and global historical narratives surrounding the contemporary Japanese environmental movement. Spanning the era of Japanese industrial pollution in the 1960s and the more recent rise of movements addressing global environmental problems, it shows how Japanese activists influenced approaches to environmentalism and industrial pollution in the Asia-Pacific region, North America, and Europe, as well as landmark United Nations conferences in 1972 and 1992. Transnational Japan in the Global Environmental Movement will appeal to scholars and students interested in the development of civil society, social movements, and environmentalism in contemporary Japan; grassroots inter-Asian connections in the postwar period.